The Effectiveness of Dialogue Journals in Improving the Skill in Writing Narrative Texts - Mukti, Ali (IJEE (Indonesian Journal of English Education), 2016)
ABSTRACT This study was conducted to investigate the effectiveness of dialogue journals technique in improving studentsâ skill in writing narrative texts. The subjects were the year-12 of IPA students of MAN 3 Malang in the academic year 2008-2009. This study involved two intact groups of students. The experimental group was given weekly journal writing, while the control group followed the regular writing. At the end of the treatment, a writing test on narrative was assigned and the studentsâ works were scored using ESL Composition Profile. The result of analysis using ANCOVA indicated that not all of the mean score of writing components of the two groups were significantly different. However, the mean score of holistic aspects was significantly different. Besides, studentsâ responses showed a positive evaluation on the implementation of dialogue journals technique. ABSTRAK Penelitian ini dilakukan untuk meneliti keefektifan teknik dialogue journal dalam meningkatkan keterampilan siswa menulis teks naratif. Subyek penelitian ini adalah siswa kelas XII IPA MAN 3 Malang tahun pelajaran 2008-2009. Penelitian ini melibatkan dua kelompok siswa. Kelompok eksperimen diminta untuk menulis dan mengumpulkanÂ  jurnal tiap pekan sementara kelompok control tetap mengikuti pelajaran menulis seperti biasa. Pada akhir perlakuan, kedua kelompok siswa diminta menulis teks naratif yang kemudian dinilai menggunakan ESL Composition Profile. Setelah dianalisa menggunakan ANCOVA,Â  hasilnya menunjukkan bahwa tidak semua nilai rerata dari tiap komponen menulis kedua kelompok berbeda secara signifikan. Akan tetapi, nilai rerata aspek secara keseluruhan berbeda secara signifikan. Disamping itu, siswa menanggapi positif terhadap penggunaan teknik dialogue journal. How to Cite: Mukti, A. (2016). The Effectiveness of Dialogue Journals in ImprovingÂ  the Skill in Writing Narrative Texts. IJEE (Indonesian Journal of English Education), 3(1), 1-14 doi:10.15408/ijee.v3i1.4064 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.4064